First lessons from the ‘Austrian patient questionnaire’ for chronic conditions in Austria - Stein, K. Viktoria (Igitur, Utrecht Publishing & Archiving, 2009)
AIMS AND OBJECTIVES: Integrated care presumes the chronic patient as its main target group. Data are sparse on demands and satisfaction of these patients with service delivery and system performance in Austria. Therefore, several surveys among patients with different chronic diseases were performed. The analysis and comparison of the patient questionnaires is aimed at collecting data on patients' needs and their priorities in chronic care within the Austrian health system. METHODS: The patient questionnaire is anonymous, structured and self-administered, with around 70 questions for each condition. The questions are standardised with the possibility of adapting them to fit the respective disease and adding additional disease-specific questions to the list. They are developed with patient focus groups in order to ensure relevance for the patients. The questionnaires are distributed nation-wide through doctor's offices and out-patient clinics. The statistical analysis of the base line data is conducted with SPSS. RESULTS: The analysis of the questionnaires highlights priorities for action in the care for chronic patients and will enable researchers and decision makers to target systems reforms and programmes more specifically. First preliminary results are now available for asthma, diabetes, chronic pain, anxiety/depression, multiple sclerosis, Parkinson's disease and age-related macular degeneration (AMD). An emphasis is laid on the cooperation between specialists and family physicians. Patients value the possibility of an extensive conversation with the attending physician higher than the possibility of freedom of symptoms. Other major issues are a well-informed physician and communication between doctors. CONCLUSIONS: For the Austrian integrated care community, the results give valuable insight into the priorities chronic care patients have concerning their interactions with the health care system and where to focus the efforts of developing new models of care.